Efficacy of a transdiagnostic ecological momentary intervention for improving self-esteem (SELFIE) in youth exposed to childhood adversity: study protocol for a multi-center randomized controlled trial - Daemen, Maud; Postma, Mary Rose; Lindauer, Ramon; Hoes-van der Meulen, Iris; Nieman, Dorien; Delespaul, Philippe; Breedvelt, Josefien Johanna Froukje; van der Gaag, Mark; Viechtbauer, Wolfgang; Schruers, Koen; van den Berg, David; Bockting, Claudi; et al. (Trials, 2021)
Targeting low self-esteem in youth exposed to childhood adversity is a promising strategy for preventing adult mental disorder, but psychological help remains difficult to access and accept for youth, calling for novel, youth-friendly approaches. Mobile Health (mHealth) and, most prominently, ecological momentary interventions (EMIs) provide a unique opportunity to deliver youth-friendly, personalized, real-time, guided self-help interventions. The aim of this study is to investigate the efficacy of a novel, accessible, transdiagnostic ecological momentary intervention for improving self-esteem (‘SELFIE’) in youth with prior exposure to childhood adversity.
Gesehen am 13.09.2023